Implementasi Sistem Informasi Website sebagai Sarana Digital dalam Mendukung Pengembangan Pariwisata di Desa Kembangbelor Mojokerto - Sholihah Ayu Wulandari; Mochammad Rifki Ulil Albaab; Adi Sucipto; Dhony Manggala Putra; Rifqi Aji Widarso; Nensyah Permadani; Dimas Aswito (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Tourism is a crucial sector for Indonesia's economic growth, yet it faces challenges in resource utilization and effective promotion. Kembangbelor Village, Mojokerto Regency, boasts attractive natural potential but remains suboptimal in popularity. This community engagement aims to bridge this gap by integrating digital technology into tourism management and promotion. The methodology includes planning, preparation, implementation, and evaluation phases. The engagement resulted in an informative website that enhances access to destination information, boosts tourist visits, and increases community participation in tourism management. Local community involvement in the evaluation phase provided feedback to enhance system sustainability. Results showed a significant increase in tourist visits post-website launch, highlighting the program's success in enhancing exposure and attractiveness of Kembangbelor Village tourism. Practical implications underscore the importance of digital technology in supporting sustainable tourism growth at the local level.